Utility of Ischemic Signs from Initial ECG in Detecting Culprit Vessels in NSTE-ACS Patients - Wijaya, Michael Asby; Putra, Teuku Muhammad Haykal; Widodo, Wishnu Aditya (The Indonesian Heart Association, 2025)
In “Utility of Ischemic Signs from Initial ECG in Detecting Culprit Vessels in NSTE-ACS Patients” (Indonesian Journal of Cardiology, 44(3), 111-9. https://doi.org/10.30701/ijc.1321), there is an errorsnoted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1321. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1321